(x-1)(2x)(x-4)=40

Simple and best practice solution for (x-1)(2x)(x-4)=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-1)(2x)(x-4)=40 equation:


Simplifying
(x + -1)(2x)(x + -4) = 40

Reorder the terms:
(-1 + x)(2x)(x + -4) = 40

Remove parenthesis around (2x)
(-1 + x) * 2x(x + -4) = 40

Reorder the terms:
(-1 + x) * 2x(-4 + x) = 40

Reorder the terms for easier multiplication:
2x(-1 + x)(-4 + x) = 40

Multiply (-1 + x) * (-4 + x)
2x(-1(-4 + x) + x(-4 + x)) = 40
2x((-4 * -1 + x * -1) + x(-4 + x)) = 40
2x((4 + -1x) + x(-4 + x)) = 40
2x(4 + -1x + (-4 * x + x * x)) = 40
2x(4 + -1x + (-4x + x2)) = 40

Combine like terms: -1x + -4x = -5x
2x(4 + -5x + x2) = 40
(4 * 2x + -5x * 2x + x2 * 2x) = 40
(8x + -10x2 + 2x3) = 40

Solving
8x + -10x2 + 2x3 = 40

Solving for variable 'x'.

Reorder the terms:
-40 + 8x + -10x2 + 2x3 = 40 + -40

Combine like terms: 40 + -40 = 0
-40 + 8x + -10x2 + 2x3 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-20 + 4x + -5x2 + x3) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-20 + 4x + -5x2 + x3)' equal to zero and attempt to solve: Simplifying -20 + 4x + -5x2 + x3 = 0 Solving -20 + 4x + -5x2 + x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 5d-33=7.2 | | 32x=5x-14 | | r/3-4=3 | | 3x-(2x-1)=5x+1-4x | | 60+.50(100)=1.30(100) | | -5.26+.21x=19.94 | | 7cos(7x)=0 | | 16x^2-4x+5-(16x^2-8x)+1=0 | | -12x-11=-47 | | 7(-8x)= | | -4x=12-x^2 | | -z-9=3.4(2z+4.3) | | -5.26+.21x=15.74 | | 20x-16y=48 | | 24x-9=18x-1 | | 85-65=x | | -3(x-1)+8(x-4)=6x+7-5x | | 5x+18+7x-14=180 | | 5x+3=10x+6 | | x^4-6x^3+6x^2+24x-40=0 | | 3x^3+3y^3+9xy+5=0 | | p^2+8p+16=1 | | -3bc^4(4b^2-8b^6c^5+5c^5)= | | 7x^2-11y=0 | | 5x(x^2-2x-1)=0 | | 3.4f-.5=2f+.5 | | X-3=51.28 | | 2(-6-3)=4(-6)3 | | 14+5y=50-4t | | (-4t^2+7t-2)+(5t^2+3t+1)= | | 60+.50x=1.30x | | 2(-6-3)=4(-6)+3 |

Equations solver categories